Intestinal Tumorigenesis Mechanisms of Development & Progression - Yang, Vincent W.; Yang, Vincent W.; Bialkowska, Agnieszka B.; Bialkowska, Agnieszka B. (Springer International Publishing : Imprint: Springer, 2015)
This volume includes the information necessary to understand recent critical advances in the mechanisms of intestinal tumorigenesis and to comprehend the complexity of the process. The volume aims to entice new researchers to participate in relevant studies, and to provide a forum for discussion within the scientific community to shape future research in this field. Discoveries in intestinal tumorigenesis lead to further understanding of mechanisms involved in colon cancer. Additionally, advancements in techniques and methods open the doors for new approaches to better define the molecular and organismal mechanisms of intestinal tumorigenesis. Chapters are authored by widely published authorities in the field. Each year, there are close to 150,000 new cases of colorectal cancer, which results in approximately 50,000 deaths per year in the United States; these figures render colorectal cancer a significant health concern. Studies attempting to understand the mechanisms of development and progression of colorectal cancer have been ongoing for decades and each year brings new discoveries yielding a better comprehension of the underlying processes at work.